A produção e a compreensão do humor por uma criança bilíngue: um estudo de caso - Mroczinski, Anna Carolina Saduckis [UNESP] (2015)
This research aims to analyze the understanding of the mood in the child L. (9 years), bilingual (Portuguese and German), from filming in which she interacts with her mother, in German, and with another child in Portuguese. The videos were transcribed according to the rules of CHAT tool, the CLAN program, designed for the project CHILDES (MACWHINNEY, 2000). For this analysis, we observed the language mechanisms that lead to understand the humour in both languages, from a dialogical discourse theoretical approach (Bakhtin, 1988,1997,1999) and studies on humour in the child's language (AIMARD, 1988; DEL RÉ, 2010, 2011, forthcoming). The theory by Bakhtin - for which the language is social and ideological, and according to which social practices influence the sense of relationship that people do things - it seems to meet the needs of the corpus in question has, as we took into account the contexts that involve interactions, as well as the subject and the verbal and non-verbal relations that are produced and that are established in different situations. Thus, the language can not be separated from its ideological content, because those are discursive and ideological brands that define the genre of this discourse. With regard to bilingualism, linguistic phenomenon complex and much discussed, it is put to understand the bilingual child as a person who acquires two languages simultaneously, before three years of age (HOUWER, 1990), regardless of the level of competence they have these languages (BULLIO, 2012). In these situations of shooting, where L. is in a natural, relaxed, which makes interactions in PB and German spontaneously, we start from the assumption that there is a distinction in the production and comprehension of humor, in both languages and if there were questioning domain difference in one of the languages by L .. Thus, from the analysis, we found that the interactions with the other child in PB, are more playful, less focused...